2016
DOI: 10.1128/microbiolspec.vmbf-0004-2015
|View full text |Cite
|
Sign up to set email alerts
|

The Structure and Function of Type III Secretion Systems

Abstract: ARTICLE SUMMARY Type III secretion systems (T3SS) afford gram-negative bacteria a most intimate means of altering the biology of their eukaryotic hosts — the direct delivery of effector proteins from the bacterial cytoplasm to that of the eukaryote. This incredible biophysical feat is accomplished by nanosyringe “injectisomes,” which form a conduit across the three plasma membranes, peptidoglycan layer and extracellular space that form a barrier to the direct delivery of proteins from bacterium to host. The fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
68
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(68 citation statements)
references
References 173 publications
(259 reference statements)
0
68
0
Order By: Relevance
“…Recent advances in assembly, structure, and mechanistic studies have considerably increased our current understanding of the function of this macromolecular complex (62)(63)(64)(65). Despite this, there are still several gaps in our knowledge on the molecular mechanisms underlying effector protein translocation into host cells.…”
Section: Discussionmentioning
confidence: 99%
“…Recent advances in assembly, structure, and mechanistic studies have considerably increased our current understanding of the function of this macromolecular complex (62)(63)(64)(65). Despite this, there are still several gaps in our knowledge on the molecular mechanisms underlying effector protein translocation into host cells.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have revealed many mechanisms that are important for disease and environmental adaptation, including extracellular enzymes (protease, mannanase, etc. ), extracellular polysaccharides (EPS), diffusible signal factor (DSF)‐dependent cell–cell signalling, and proteins secreted by the type II secretion system (T2SS), type III secretion system (T3SS), type IV secretion system (T4SS) and more recently type VI secretion system (T6SS) (He and Zhang, ; Büttner and Bonas, ; Ryan et al , , ; Notti and Stebbins, ; Zhou et al , ). In Xcc , one of the best‐studied mechanisms that contributes to virulence is the T3SS apparatus.…”
Section: Introductionmentioning
confidence: 99%
“…Seven T3SS injectisome families have been identified (9) and share a number of homologous membrane-associated components with the flagellar basal body (10). While many aspects of T3SS structure are similar among different T3SS families, the repertoire of encoded T3SS effector proteins is unique for each genus or even species (11,12). For example, pathogenic Yersinia species, which include the plague agent Yersinia pestis and the enteropathogens Yersinia enterocolitica and Yersinia pseudotuberculosis, and the opportunistic pathogen Pseudomonas aeruginosa encode a Ysc family T3SS that contributes to virulence.…”
mentioning
confidence: 99%